A contribution to the taxonomy of the genus Pelecium Kirby (Coleoptera: Carabidae: Peleciini) - Orsetti, Artur; Lopes-Andrade, Cristiano (European Journal of Taxonomy, 2024)
Pelecium Kirby, 1817 is a neotropical genus of flightless carabid beetles comprising 34 species, distributed from Panama to middle Argentina. Most species of Pelecium are known from short series and few localities, in some cases only from the holotype. Male and female abdominal terminalia are not described for the majority of the species, a situation that makes it difficult to describe new species or to study intraspecific variation. Here, we describe nine new species based on individuals from Brazil: Pelecium buckupi sp. nov., P. fistulosus sp. nov. and P. zaguryi sp. nov. from the Centre-West region, P. belloi sp. nov., P. chrissquirei sp. nov., P. straneoi sp. nov. and P. zophos sp. nov. from the Southeast region, and P. balli sp. nov. and P. grossii sp. nov. from the South region. We also provide new distributional records and descriptions of abdominal terminalia for twelve species: Pelecium atroviolaceum Straneo & Ball, 1989, P. bolivianum Straneo & Ball, 1989, P. cyanipes Kirby, 1817, P. helenae Straneo & Ball, 1989, P. laeve Chaudoir, 1854, P. negrei Straneo, 1962, P. drakei Quedenfeldt, 1890, P. punctatostriatum Straneo, 1970, P. purpureum Straneo, 1955, P. rotundipenne Schaum, 1860, P. striatum Straneo, 1955 and P. violaceum Brullé, 1838.